2020
DOI: 10.1111/1753-6405.13038
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of homelessness on mortality: a 15‐year Australian cohort study

Abstract: Objective: To examine the effect of homelessness on mortality. Methods: This 15-year retrospective longitudinal cohort study compared mortality outcomes of homeless and non-homeless adults attending the emergency department of an innercity public hospital in Melbourne, Victoria between 1 January 2003 and 31 December 2004. Homeless individuals had ≥1 recorded episodes of homelessness within the recruitment period, categorised by type: primary, secondary, tertiary, marginally housed. Non-homeless individuals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Homelessness is also linked to an increase in morbidity (Nielsen et al, 2011) and multi-morbidity (Bowen et al, 2019), and longitudinal studies (Aldridge et al, 2019;Nordentoft & Wandall-Holm, 2003;Seastres et al, 2020;Stenius-Ayoadeet al, 2017) show that homelessness is associated with higher mortality. For example, the homeless in Copenhagen hostels are four times more likely than the general population to die early (Nordentoft and Wandall-Holm, 2003), while homelessness in Finland is linked to a five-fold increase in mortality (Stenius-Ayoadeet al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homelessness is also linked to an increase in morbidity (Nielsen et al, 2011) and multi-morbidity (Bowen et al, 2019), and longitudinal studies (Aldridge et al, 2019;Nordentoft & Wandall-Holm, 2003;Seastres et al, 2020;Stenius-Ayoadeet al, 2017) show that homelessness is associated with higher mortality. For example, the homeless in Copenhagen hostels are four times more likely than the general population to die early (Nordentoft and Wandall-Holm, 2003), while homelessness in Finland is linked to a five-fold increase in mortality (Stenius-Ayoadeet al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the homeless in Copenhagen hostels are four times more likely than the general population to die early (Nordentoft and Wandall-Holm, 2003), while homelessness in Finland is linked to a five-fold increase in mortality (Stenius-Ayoadeet al, 2017). In Australia, homelessness is related with an almost two-fold greater risk of mortality over a 15year period and an approximately 12-year reduction in age at death when compared to non-homeless emergency department attendees (Seastres et al, 2020). When compared to the general population, this is estimated to be a nearly four-fold increase in mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that financial deprivation has a strong association with poor health status. People in this vulnerable and isolated situation are particularly affected by health problems which are associated with higher rates of premature mortality [4][5][6][7]. Harsh living conditions, including the street and crowded shelters, increase the risk of infectious diseases like hepatitis C and HIV [8,9], respiratory infections, hepatitis B [10] or different skin infections (pediculosis, scabies) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research from Australia and internationally has demonstrated that people experiencing homelessness have a high prevalence of a range of physical and mental health conditions that result in high rates of morbidity and mortality 15-17 . The homeless are also known to be less likely to access primary and preventive healthcare services resulting in their health needs being unaddressed until they present as seriously ill with a medical crisis at hospital emergency departments 13,14,18 .…”
mentioning
confidence: 99%